Preexisting ulcerative colitis increases the risk of immune-related colitis and predicts divergent survival outcomes in gastrointestinal cancer patients treated with immune checkpoint inhibitors - Xu, Shuo; Chen, Lu; Liu, Kaixuan; Tao, Hui; Ji, Zhengzheng; Wu, Jiamin; Zhao, Yuanyi; Zhou, Qiankun; Li, Liuying; Zhu, Hanlong; Wang, Yunzhe; Wang, Fangyu (Frontiers in Immunology, 2025)
BackgroundThe risk of immune-related colitis (IRC) and efficacy of immune checkpoint inhibitors (ICIs) in patients with gastrointestinal cancers and preexisting ulcerative colitis (UC) has not been well described.Patients and methodsWe divided the patients with gastrointestinal cancers and preexisting UC who received ICIs between January 2021 and May 2024 into two groups as IRC group and non-IRC group. The electronic medical records were reviewed to compare the risk of IRC between two groups. Survival analysis and COX regression was conducted to assess clinical efficacy.ResultsOf the 138 patients in study, 31 patients had a history of UC prior to initiation of immunotherapy. IRC occurred in 22 patients (71.0%) and over half experienced severe IRC (54.5%), a rate higher than that among similar patients without underlying UC (17.4%, p = 0.013). Compared with patients without UC who did not experience IRC, PFS and OS of patients with UC who had mild IRC were longer (PFS: 170 vs 96 days, p < 0.001; OS: 261 vs 172 days, p = 0.021) and those with severe IRC demonstrated merely a marginal advantage in terms of PFS (147 vs 96 days, p = 0.001), but no significant difference was observed in OS (171 vs 172 days, p = 0.851). The Multivariate analysis affirmed that mild IRC were correlated with a favorable prognosis (HR = 0.286, 95%CI: 0.106-0.769, p = 0.013), whereas severe IRC was not sufficient to be recognized as independent risk factors affecting survival outcomes. (HR = 1.149, 95%CI: 0.502-2.633, p = 0.742). The result of serum cytokines showed that the levels of IL-6 and IL-17A in patients with IRC were significantly elevated.ConclusionFor preexisting UC patients treated with ICIs, the risk of IRC is increased. Mild IRC may suggest a favorable prognosis, and being vigilant and effectively managing the occurrence of severe IRC is crucial for maximizing clinical benefits. Targeting the IL-6 pathway may be a potential new strategy for treating IRC in the future.